2021
DOI: 10.1177/11786329211017411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Public Health Insurance on Out-of-Pocket Health Expenditures of the Near-Poor in Vietnam

Abstract: Out-of-pocket payment is one of the indicators measuring the achievement of Universal Health Coverage. According to the World Health Organization, for countries from the Asia Pacific Region, out-of-pocket payments should not exceed 30%-40% of total health expenditure. This study aimed to identify factors influencing out-of-pocket payment for the near-poor for outpatient healthcare services as well as across health facilities at different levels. The data of 1143 individuals using outpatient care were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…particularly the out-of-pocket costs. Although, social health insurance has been shown to decrease the out-of-pocket costs of patients (21,22), they can still be notable (23,24). These out-of-pocket costs are particularly important to investigate in the context of critical care, due to its potentially high costs; which may mean they remain significant even for patients that are covered by insurance.…”
Section: Introductionmentioning
confidence: 99%
“…particularly the out-of-pocket costs. Although, social health insurance has been shown to decrease the out-of-pocket costs of patients (21,22), they can still be notable (23,24). These out-of-pocket costs are particularly important to investigate in the context of critical care, due to its potentially high costs; which may mean they remain significant even for patients that are covered by insurance.…”
Section: Introductionmentioning
confidence: 99%
“…At present, China's basic medical insurance system still does not provide a high reimbursement level for outpatient care. It is universally accepted that a reasonable OOP proportion is 30%–40% for health expenditures [ 54 ], but, as of 2018, the OOP proportion of outpatient care for middle-aged and elderly people in China was 86.79% according to this study. Additionally, there are still dramatical discrepancies in security level between different insurance insurances in China—for example, the reimbursement level of resident medical insurance is lower than that of employee medical insurance [ 35 , 38 ], which may lead to different IOp of health service utilization for middle-aged and elderly people having different medical insurances.…”
Section: Discussionmentioning
confidence: 65%
“…Under Decision 139/2002/QD-TTg, dated 15 October 2002, the Healthcare Fund for the Poor was introduced, where the poor and ethnic minorities had SHI premium exemption and medical treatments. Decree 63/2005/ND-CP, dated 16 May 2005, expanded the compulsory groups, particularly, children aged under six had free medical treatments, and the poor and ethnic minorities were fully subsidised by the government budget in purchasing SHI cards. The SHI Law was first introduced in 2008 under Law No.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted to estimate the incidence of CHEs and impoverishment in Vietnam (see, for instance, [ 12 , 13 , 14 , 15 , 16 ]). Using data sets from the Vietnam Household Living Standard Survey (VHLSS) conducted in 1993 and 1998, [ 13 ] found that CHEs in Vietnam decreased from 9.3 per cent to 7.8 per cent in this period.…”
Section: Introductionmentioning
confidence: 99%